THE ‘CALVATONE HOARD 2018’ (BEDRIACUM, CREMONA): ASSESSING THE COINAGE AND ICONOGRAPHY OF GALLIENUS IN 3RD-CENTURY AD ITALY - Antonino Crisà, (PEOPLE: International Journal of Social Sciences, 2026)
The archaeological site of Calvatone (province of Cremona – Italy), known as the ancient Bedriacum, represents an exceptional case study within the regional context of the Gallia Cisalpina province. Since the 1980s, the University of Milan is conducting archaeological excavations at Calvatone exploring substantial areas of the settlement including private houses, storing, manufacturing and commercial sectors. According to numismatic data and coin analysis, we know that the site economy was extremely dynamic showing prevalent commercial exchanges between the small city and other countryside centres of the Gallia Cisalpina region. Also, the proximity to the Oglio River and the Via Postumia, the Roman road connecting Genoa with Aquileia, was crucial to ease such commercial activities. In 2018, archaeologists working at Bedriacum’s site discovered a new Roman treasure containing 144 silver coins (antoniniani) issued during the reign of Gallienus (253-68 AD). The “Calvatone Hoard 2018” has been properly cleaned, studied and then exhibited in the local city council Visitor Center. The scope of my paper is to outline such a discovery in light with the complex system of symbols and iconography utilized by Gallienus to promote his political and military plans. This includes symbols of the Roman legions and animals, such as the lion and the deer. First, I outline the coin treasure and the historical context to which the hoard is linked to better contextualize the discovery in the wider framework of the Roman Imperial history. Then, I assess the hoard showing a series of essential coin obverse and reverse types proving the attempts of Gallienus to spread out his iconographic and symbolic plan of “advertising” his political and military action program. Finally, the “Calvatone Hoard 2018” plays an essential role to understand how hoarding trends worked in a small community of northern Italy in the mid-3rd century AD, a traumatic period of time of Roman history, studded with usurping emperors, revolts, Barbarian invasions and violence.